Evaluation of the implementation of standard facilities and infrastructure to improve the quality of education at SMA Bina Dharma Jakarta - Aldi, Ahmad; Muljono, Hery; Ghani, Rahman; Ermawaty, Imas Ratna; Ernianis, Ernianis (Educenter : Jurnal Ilmiah Pendidikan, 2024)
The background of this research is the preparation for face-to-face learning, so we need facilities and infrastructure. where learning that started at school has become at home with the issuance of government regulation number 57 years. 2021 regarding the standard of facilities and infrastructure which is used as a reference in face-to-face learning. This study uses a qualitative evaluation research where the evaluation model used is the discrepancy model. The discrepancy model consists of four stages, namely design, installation, process and comparison. Then the results of the design used are government regulation number 57 of 2021 concerning standard facilities and infrastructure, the form of installation is a discussion with the foundation then socialized with school residents, the process is data collection, the making of proposals, spending and realization and comparison there are facilities that do not yet exist, learning process related to the quality of education are also still lacking because teachers have not mastered technology and lack of facilities and infrastructure such as laptops and webcams, it can be said that the evaluation results regarding standards facilities and infrastructure are still lacking to improve the quality of education. suggestions from researchers to hold training and re-collection of data to add facilities and infrastructure that are lacking.